Uji Wilcoxon untuk Mengevaluasi Hasil Pretest-Posttest Pembelajaran Entomologi Kedokteran pada Mahasiswa Preklinik - Fitria Dewi Puspita Anggraini; Mona Zubaidah; Khairunnida Rahma (Public Health and Safety International Journal, 2025)
This study aims to evaluate the effectiveness of medical entomology learning in preclinical students through comparative analysis of pretest and posttest results using the Wilcoxon signed-rank test. The research hypothesis states there is a significant difference between pretest and posttest scores after medical entomology learning. The research model uses a quasi-experimental design with a one-group pretest-posttest approach. The theory applied is competency-based learning evaluation concepts in medical education. Research inputs include medical entomology materials covering definitions, vector insect classification, morphology, diagnosis, vector identification, disease control, and the role of entomology in medicine. The research method employs purposive sampling technique with a structured questionnaire instrument of 10 multiple-choice questions. The sample consists of 106 preclinical students from the 2023 cohort taking medical entomology courses. Data were analyzed using the Wilcoxon signed-rank test with SPSS version 21 software and 95% confidence level. Results show significant differences between pretest and posttest scores (p < 0.05), with 83 students experiencing increased posttest scores compared to pretest. The conclusion demonstrates that medical entomology learning methods are effective in improving preclinical students' understanding of arthropods as disease vectors. This research provides empirical evidence that medical entomology learning successfully achieves the established learning objectives for preclinical students.